A study on safety performance examination of BDC/Kenyalang interchange - Imelda, Jelani (Faculty of Engineering, 2012)
Road Safety Audit is relatively new in Sarawak. Unlike in West Malaysia, where RSA has been introduced in the 90's, there is only a handful of road projects in Sarawak include RSA as part of its design requirements. In this study, the BDC Kenyalang intercharge will be used as case study and scrutinized in term of its safety to road users by conducting qualitative study on safety performance examination similar to RSA stage 5 procedures and the collection of information through series of interviews with experts from government agencies and private sectors. RSA was conducted to identify the problems such as wear and tear due to environment maturity.